A 1‐minute full brain MR exam using a multicontrast EPI sequence. Issue 6 (31st October 2017) - Skare, Stefan; Sprenger, Tim; Norbeck, Ola; Rydén, Henric; Blomberg, Lars; Avventi, Enrico; Engström, Mathias
Abstract : Purpose: A new multicontrast echo‐planar imaging (EPI)‐based sequence is proposed for brain MRI, which can directly generate six MR contrasts (T1 ‐FLAIR, T2 ‐w, diffusion‐weighted (DWI), apparent diffusion coefficient (ADC), T 2 * ‐w, T2 ‐FLAIR) in 1 min with full brain coverage. This could enable clinical MR clinical screening in similar time as a conventional CT exam but with more soft‐tissue information. Methods: Eleven sequence modules were created as dynamic building blocks for the sequence. Two EPI readout modules were reused throughout the sequence and were prepended by other modules to form the desired MR contrasts. Two scan protocols were optimized with scan times of 55–75 s. Motion experiments were carried out on two volunteers to investigate the robustness against head motion. Scans on patients were carried out and compared to conventional clinical images. Results: The pulse sequence is found to be robust against motion given its single‐shot nature of each contrast. For excessive out‐of‐plane head motion, the T1 ‐FLAIR and T2 ‐FLAIR contrasts suffer from incomplete inversion. Despite lower signal‐to‐noise ratio (SNR) and resolution, the 1‐min multicontrast EPI data show promising correspondence with conventional diagnostic scans on patients. Conclusion: A 1 min multicontrast brain MRI scan based on EPI readouts has been presented in this feasibility study. Preliminary data show potential for clinical brain MRI use with minimal bore time for the patient. Such short examination time could be useful (e.g., for screening and acute stroke). The sequence may also help planning conventional brain MRI scans if run at the beginning of an examination. Magn Reson Med 79:3045–3054, 2018. © 2017 International Society for Magnetic Resonance in Medicine.